Modern correction of an underactive bladder after spinal cord injuries - A. R. Amirov; R. A. Bodrova (National Electronic Information Consortium (NEICON), 2021)
The article presents an overview of the literature on modern correction methods of an underactive bladder in spinal cord injury patients. The article provides data on the effectiveness of treatment and possible complications.